Material Genealogies: Bronze Moulds and their Castings in Later Bronze Age Britain. (27th July 2016) - Webley, Leo; Adams, Sophia
Abstract : Bivalve bronze moulds were used for casting bronze and lead objects – mainly axes – during the Middle and Late Bronze Age. These remarkable artefacts, which were sometimes beautifully decorated, have been surprisingly little studied. This paper discusses the bronze moulds from Britain, outlining the range of possibilities that existed for the life courses of these objects during the three broad stages of manufacture, use, and deposition. Two points will be emphasised. First, it will be shown that the biographical pathways available to bronze moulds differed significantly from those of moulds made from stone or clay, which may relate to the differing properties and conceptual associations of these three materials. Secondly, the relationships between the life courses of bronze moulds and the artefacts cast in them will be explored, focusing particularly on cases in which moulds and their castings were deposited together in the same hoard. It will be suggested that the 'genealogical' link between a mould and its 'offspring' could have formed a significant element of the biography of both objects. RÉSUMÉ: Généalogies matérielles: Moules de bronze et leurs moulages à l'âge du bronze moyen et final en Grande-Bretagne de Leo Webley & Sophia Adams Des moules bivalves en bronze furent utilisés pour mouler des objets en bronze et en plomb, essentiellement des haches, pendant l'âge du bronze moyen et final. Il est surprenant que ces remarquables objets fabriqués, qui furent parfois admirablement décorés, ont été si peu étudiés. Cet article débat des moules de bronze britanniques, exposant la gamme de possibilités qui existait pour le cours de la vie de ces objets pendant les trois grands stades de la fabrication, de l'utilisation et de la déposition. Nous insisterons sur deux points. D'abord, nous montrerons que les chemins biographiques accessibles aux moules de bronze différaient grandement de ceux des moules fabriqués en pierre ou en argile, ce qui peut avoir un rapport avec les propriétés différentes et les associations conceptuelles des ces trois matériaux. Ensuite, nous explorerons les relations entre le cours de la vie des moules en bronze et les objets fabriqués moulés dedans, nous concentrant particulièrement sur les cas dans lesquels les moules et leurs objets avaient été déposés ensemble dans la même cache. Nous proposerons que le lien 'généalogique' entre un moule et son 'rejeton', aurait pu former un élément significatif de la biographie de ces deux objets. ZUSSAMENFASSUNG: Materielle Genealogien: Bronzegussformen und ihre Gussstücke im Großbritannien der späteren Bronzezei t, von Leo Webley und Sophia Adams Zweischalige Gussformen aus Bronze wurden in der mittleren und späten Bronzezeit zum Guss von Bronze- und Bleiobjekten – vor allem Äxten – genutzt. Diese auffälligen Artefakte, die manchmal reich verziert wurden, wurden bisher erstaunlich selten untersucht. Dieser Beitrag diskutiert die bronzenen Gussformen aus Großbritannien und stellt die Bandbreite der Möglichkeiten vor für den Lebensweg dieser Objekte während der drei grundsätzlichen Stufen der Herstellung, Nutzung und Deponierung. Zwei Punkte werden besonders betont: Zum einen wird gezeigt, dass die biographischen Wege, die den Gussformen aus Bronze offen standen, sich signifikant unterschieden von jenen für Gussformen aus Stein oder Ton, was mit den unterschiedlichen Eigenschaften und konzeptuellen Assoziationen dieser drei Materialen zusammenhängen mag. Zum anderen wird der Zusammenhang zwischen den bronzenen Gussformen und den in ihnen gegossenen Artefakten untersucht, wobei insbesondere auf Fälle eingegangen wird, in denen Gussformen und ihre Gussstücke zusammen in der gleichen Deponierung niedergelegt worden sind. Es wird angenommen, dass der ‚genealogische' Link zwischen einer Form und ihrem‚ Abkömmling' ein signifikantes Element in der Biographie beider Objekte gebildet haben kann. RESUMEN: Genealogías materiales: moldes de bronce y sus piezas de función durante el Bronce Medio y Final en Gran Bretaña, por Leo Webley y Sophia Adams Los moldes de bronce bivalvos se emplearon para la fundición de objetos de bronce y plomo -fundamentalmente hachas- durante el Bronce Medio y Final. Sorprendentemente estos objetos excepcionales, que están en ocasiones profusamente decorados, han sido poco estudiados. Este artículo presenta los moldes de bronce documentados en Gran Bretaña, describiendo un rango de posibilidades sobre la vida útil de este tipo de objetos durante las tres fases de manufactura, uso y deposición. Se resaltan especialmente dos aspectos. El primero refleja que la secuencia biográfica de estos moldes en bronce difiere significativamente de aquéllos realizados en piedra o arcilla, lo cual se podría relacionar con diferentes propiedades y asociaciones conceptuales de estos tres materiales. En segundo lugar, se explora la relación entre la vida útil de los moldes de bronce y las piezas fundidas, centrándose especialmente en los casos en los que ambos fueron depositados en las mismas acumulaciones. Se propone que este vínculo "genealógico" entre los moldes y su "descendencia" podría haber constituido un elemento significativo de la biografía de ambos objetos.